Ali je bila arhivistika pomožna zgodovinska veda - Tekavec, Žiga (Atlanti, 2024)
Purpose: The aim of this paper is to analyze the concept of archival science, which is often classified as an auxiliary historical science, while many scientists have justified archival studies as an independent, multidisciplinary science.Method: Through a review of literature on ancient archives, the article answers the question of whether ancient archives were created to support historiography or were established independently.Results: Chronological examination of the ancient history of archives shows that the first archives were established to assist the administration of the state and kept documentary evidence that had power in courts and international relations.Conclusion/Findings: The first archives were not created with an aim to docu-ment history, but were in the function of a notary, as the archives also certified public documents and contracts and were often publicly available. Without pub-lic ancient archives and consistent downloading, storage and transcription of materials, today we would have much worse knowledge about humanity‘s past.
Keywords: ancient archives; antični arhivi; archival science; archivi antichi; archivist; archivista; arhivist; arhivistika; auxiliary historical sciences; history of archival science; pomožne zgodovinske vede; scienza archivistica; scienze storiche ausiliarie; storia della scienza archivistica; zgodovina arhivistike